Reliability of reproducing intercuspal position by hand articulation on dental casts without using an occlusal index - Kantola, Kristina Garfjell; Møller, Guro (Universitetet i Tromsø, 2013)
The aim of this study was to examine the accuracy of reproducing maximal intercuspal position (IP) on dental casts without using a wax-index as compared with the IP determined by the wax index on the same models. The material consisted of dental casts, which were taken from 15-year old adolescents as part of oral examinations during the ”Fit Futures – part of The Tromsø Study”. All dental casts having wax bites were included in this study (N=80). Two examiners assessed Angle’s classification and overjet on all dental casts twice, first fitting the dental casts together by hand articulation without using the wax index and second time using the wax index. Differences between the first and second assessment were measured and the agreement was analyzed using Cohen’s kappa. In 49 % of the models, there was no difference in overjet measurements with or without using an occlusal index, while 21 % of the casts showed a difference of more than 0.5 mm, out of which 2 casts differed more than 1 mm. Agreement on Angle’s classification was 93 % on the right side and 91 % on the left between the two measurements. In molar millimeter measurements 16- 20% of the cases showed more than 0.5 mm difference between the assessments. An agreement on treatment need between the first and second measurement, based on overjet values, was found in 84% of the cases. The results suggest that in the majority of dental casts with permanent dentition and no extreme malocclusions, the maximal intercuspal position may be reproduced acceptably by hand articulation without a wax index. However, this method may not be reliable enough for research purposes or for planning of orthodontic treatment in some individual patients with severe occlusal deviations.